Biometric viscera and blood parameters of meat quails supplemented with inorganic selenium and vitamin E - Zancanela,Vittor (2017)
SUMMARY This study aimed to evaluate biometric viscera and blood parameters of quails at 14 and 35 days of age, supplemented with different levels of inorganic selenium and vitamin E. A completely randomized design was used in a 4×4 factorial scheme (inorganic Se = 0.1125, 0.2250, 0.3375 and 0.4500 mg/kg diet x VE = 10, 23, 36 and 49 IU/kg feed). In the 0-14 days experiment, 2,400 newborn quail were used, distributed in 16 treatments and three replications of 50 birds each. In the 14-35 days experiment, 1,680 14 day-old quails were used with same treatments and three replicates of 35 birds each. At 14 days, the relative spleen weights (P=0.0203) increased linearly as a function of the VE level, while at 35 days, the relative weight of the bursa (P=0.0390) increased linearly as a function of Se concentration. At 14 days, there was a vitamin x mineral interaction (p=0.0097) affecting total cholesterol (TC), and a quadratic effect (P = 0.0138) related to Se and linear reduction levels (P=0.0275) as a function of VE. At 35 days, the TC concentrations (P=0.0055) and triglycerides (TG, P = 0.0220) showed a quadratic effect for Se. The linear increase in spleen weight and bursa after 14 and 35 days respectively suggests an improved immune response as a function of VE and Se supplementation. To achieve the lowest concentration of TC and TG at 35 days of age, supplementation of 0.26 and 0.29 mg/Se/kg/feed, respectively, is recommended.